Multifunctional Desferrichrome Analogues as Versatile (89)Zr(IV) Chelators for ImmunoPET Probe Development - Adams, Casey J. (Mol Pharm, 2017)
New bifunctional hexa- and octadentate analogues of the hydroxamate-containing siderophore desferrichrome (DFC) have been synthesized and evaluated as (89)Zr-chelating agents for immunoPET applications. The in vitro and in vivo inertness of these new ligands, Orn3-hx (hexadentate) and Orn-4hx derivatives (octadentate), was compared to the gold standard hexadentate, hydroxamate-containing chelator for (89)Zr desferrioxamine (DFO). Density functional theory was employed to model the geometries of the resulting Zr(IV) complexes and to predict their relative stabilities as follows: Zr(Orn4-hx) > Zr(DFC) > Zr(Orn3-hx). Transchelation challenge experiments of the corresponding radiochemical complexes with excess ethylenediaminetetraacetate (EDTA) indicated complex stability in accordance with DFT calculations. Radiolabeling of these ligands with (89)Zr was quantitative (0.25 μmol of ligand, pH 7.4, room temperature, 20 min). For antibody conjugation, the isothiocyanate (NCS) functional group was introduced to the N terminus of Orn3-hx and Orn-4hx. An additional trifunctional derivative that bears a silicon-rhodamine fluorophore on the C-terminus and NCS on the N terminus was also furnished. As proof of concept, all NCS derivatives were conjugated to the HER2-targeting antibody, trastuzumab. Radiolabeling of immunoconjugates with (89)Zr was accomplished with radiochemical yields of 16 ± 2% to 95 ± 2%. These constructs were administered to naive mice (male, C57BL/6J, n = 4) to assess in vivo inertness, which is inversely correlated with uptake of (89)Zr in bone, after 96 h circulation time. We found bone uptake to range from 7.0 ± 2.2 to 10.7 ± 1.3% ID/g, values that compare well to the corresponding DFO conjugate (7.1 ± 0.8% ID/g). In conclusion, we have rationally designed linear, bifunctional and trifunctional desferrichrome analogues suitable for the mild and inert radiolabeling of antibodies with the radionuclide (89)Zr.